Transformation of Local Wisdom in the Practice of Islamic Da’wah: A Socio-Cultural Analysis in South Sulawesi - Muhammadong Muhammadong (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study analyzes the evolution of indigenous knowledge within the context of Islamic da'wah in South Sulawesi, focusing on social and cultural dimensions. This research is predicated on the premise that Islamic da'wah in South Sulawesi evolves within a social framework influenced by persistent local cultural values and traditions. In this context, local wisdom serves as both a cultural identity and a strategic vehicle for disseminating Islamic doctrines. This research seeks to examine the transformation of local wisdom within Islamic da'wah methods and to discern its social and cultural ramifications. The study utilized a qualitative methodology using a descriptive-analytical framework. Data were gathered by library research, observation, and comprehensive interviews with religious leaders, traditional leaders, and community people engaged in culturally oriented da'wah activities. The results indicate that the evolution of local wisdom transpires through the adaptation, accommodation, and reinterpretation of indigenous cultural values within the context of Islamic teachings. This method makes da'wah more acceptable to society, enhances social integration, protects local cultural identity, and encourages a moderate, inclusive, and contextual type of religiosity.